Improving of Junior High School Visual Thinking Representation Ability in Mathematical Problem Solving by CTL - Edy Surya; Jozua Sabandar; Yaya S. Kusumah; Darhim Darhim (Journal on Mathematics Education, 2013)
The students' difficulty which was found is in the problem of understanding, drawing diagrams, reading the charts correctly, conceptual formal mathematical understanding, and mathematical problem-solving. The appropriate problem representation is the basic way in order to understand the problem itself and make a plan to solve it. This research was the experimental classroom design with a pretest-posttest control in order to increase the representation of visual thinking ability on mathematical problem-solving approach with contextual learning. The research instrument was a test, observation, and interviews. Contextual approach increases of mathematical representations ability increases in students with high initial category, medium, and low compared to conventional approaches.